2018
DOI: 10.1002/jcb.26441
|View full text |Cite
|
Sign up to set email alerts
|

RECK inhibits cervical cancer cell migration and invasion by promoting p53 signaling pathway

Abstract: The present study was conducted to investigate the effects of RECK on cervical cancer cell migration and invasion to help understand relevant molecular mechanisms. QRT-PCR and western blot were respectively utilized to examine the transcriptional and translational levels of RECK in cervical cancer cell lines (HELA and C33A) and normal cell line (H8). After transfection with RECK overexpressing vectors, the expression of RECK mRNA, RECK and p53 signaling pathway-related proteins (p21, p53, bcl-2, and Bax) in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…EMT was also notably suppressed, as demonstrated by the downregulation of N-cadherin, snail and twist expression, which are well documented markers of EMT (37,38). (41,42), in addition to inhibiting cancer cell migration (43)(44)(45). TP53 activation has also been previously reported to serve an inhibitory role in the EMT process, in human oral mucosal fibroblasts and oral submucous fibrosis by downregulating N-cadherin expression (46) and in colorectal cancer cells by downregulating Snail expression (37), which are findings consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…EMT was also notably suppressed, as demonstrated by the downregulation of N-cadherin, snail and twist expression, which are well documented markers of EMT (37,38). (41,42), in addition to inhibiting cancer cell migration (43)(44)(45). TP53 activation has also been previously reported to serve an inhibitory role in the EMT process, in human oral mucosal fibroblasts and oral submucous fibrosis by downregulating N-cadherin expression (46) and in colorectal cancer cells by downregulating Snail expression (37), which are findings consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…27 As illuminated previously, RECK impaired the malignant development of several tumors including CC. [28][29][30] Moreover, the methylation of RECK in several cancers has certified to predict poor prognosis, [31][32][33] while the potential mechanism has not been discussed in detail. Consistently, our research also revealed the tumor inhibitor role of RECK in HPV-positive CC cells and the accumulated H3K27me in the RECK promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the upregulation of p53 in cancer cells may prevent cancer cell proliferation by promoting cell cycle arrest and apoptosis ( 33 36 ). Liu et al ( 37 ) revealed that the p53 pathway in human cervical cancer cells is activated by reversion-inducing-cysteine-rich protein with Kazal motifs overexpression, which induces cancer cell apoptosis and reduces migration. In the present study, erianin treatment of HeLa cells could promote the activation of p53.…”
Section: Discussionmentioning
confidence: 99%